Anchusella cretica (Boraginaceae): a new genus and species record for the flora of Kosovo (Southeast Europe) - Elez Krasniqi; Naim Berisha (Biodiversity Data Journal)
Anchusella cretica (Boraginaceae) is recorded for the first time in Kosovo and represents a new genus and species for the national flora. This range extension improves the knowledge about floristic and biogeographic patterns in the Western Balkans. Based on fieldwork in 2024–2025, four distinct populations were identified in dry, rocky, calcareous grasslands of the sub-Mediterranean region. The species shows a limited extent of occurrence (EOO = 80 km²) and area of occupancy (AOO = 5.54 km²) is limited. It is therefore assessed as Near Threatened (NT) at national level according to IUCN criteria. This finding emphasizes the importance of further botanical surveys and the conservation of underexplored lowland habitats in Kosovo.new records, flora, Boraginaceae, distribution, range extension, Balkans